Situating Interprofessional Education Curriculum within a Theoretical Framework for Productive Engaged Learning: Integrating Epistemology, Theory, and Competencies - Azzam, Mohammad; Puvirajah, Anton (Journal of Research in Interprofessional Practice and Education)

(untitled) (Canadian Institute for Studies in Publishing Press (Simon Fraser University at Harbour Centre), 2024)
Interprofessional education (IPE) has a longstanding presence in the health and social care (HASC) professions, by which its sustainable implementation in HASC professional education has the potential to effectively prepare HASC professional students for interprofessional collaborative practice (IPCP). Implementation of IPE has increased over the last two decades with the emergence of a curriculum guided by constructivist epistemology and learning theories that emphasize demonstrating competence in practice. Nonetheless, since IPE first emerged in the early 1960s, most IPE initiatives have been sporadic and lacked guidance through theoretical underpinnings. This conceptual article first discusses why it is important to have theory drive HASC professional education. Next, it explores what is meant by curriculum, followed by a discussion on the importance of curriculum theory to HASC professional education processes. This article then illustrates the learning theories arising from behaviourist and constructivist epistemologies that inform curriculum theory in the HASC professions, with particular emphasis on how constructivist learning theories inform IPE. Lastly, the article proposes a theoretical framework for productive engaged learning through which IPE opportunities may be grounded, leading to student proficiency in interprofessional professional competencies (knowledge, skills, and dispositions), establishment of professional communities of practice, and eventual improvement of patient/client-oriented outcomes.